Interrogating the Efficacy of Public Service Personnel Training at the Kenya School of Government - Chirchir Matthew Kimeli (The European Educational Researcher, 2019)
The purpose of this study was to evaluate the efficacy of senior management training on transfer of learning among public officers trained by Kenya school of Government by establishing whether training interventions yield corresponding increase in the level of trainees’ knowledge, skills and attitude. F-test was used to find out whether there was any variance within the pretest and posttest samples, paired sample t- test and analysis of variance was used to statistically determine significant difference between posttest and pretest mean scores of 197 trainees who attended senior management course offered at Kenya School of Government in Kenya sampled through single stage cluster sampling technique. The study concluded that mean scores of the posttest trainee’s knowledge level and application/use were different from the mean scores of the trainee pretest scores suggesting a change in the trainees’ level of knowledge and applicability of the training to trainees’ work following the training intervention. Furthermore, the scores showed a positive change from the pretest to posttest. Nonetheless, it was noted that trainee’s perception of how important it is to learn a specific set of skills (attitude) does not change even after training intervention is administered. The study provides training effectiveness roadmap for Kenya school of Government to address assessment gap noted and provides an empirical rationale for Governments and corporate organizations to commit and make major investments on training of their employees as a useful way of staff capacity building towards enhanced employee performance.